2022
DOI: 10.3390/antiox11122374
|View full text |Cite
|
Sign up to set email alerts
|

Citrus Essential Oils in Aromatherapy: Therapeutic Effects and Mechanisms

Abstract: Citrus is one of the main fruit crops cultivated in tropical and subtropical regions worldwide. Approximately half (40–47%) of the fruit mass is inedible and discarded as waste after processing, which causes pollution to the environment. Essential oils (EOs) are aromatic compounds found in significant quantities in oil sacs or oil glands present in the leaves, flowers, and fruit peels (mainly the flavedo part). Citrus EO is a complex mixture of ~400 compounds and has been found to be useful in aromatic infusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 191 publications
1
31
0
3
Order By: Relevance
“…Many parts of this plant, including leaves, stem, and fruit, can be extracted into oil (Aran et al, 2021). Essential oils from citrus plants have been used in the cosmetic, pharmaceutical, perfumery, and cleaning industries (Agarwal et al, 2022). Patchouli, jasmine, and roses are flowering plants grown by the community to decorate their homes and yards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many parts of this plant, including leaves, stem, and fruit, can be extracted into oil (Aran et al, 2021). Essential oils from citrus plants have been used in the cosmetic, pharmaceutical, perfumery, and cleaning industries (Agarwal et al, 2022). Patchouli, jasmine, and roses are flowering plants grown by the community to decorate their homes and yards.…”
Section: Discussionmentioning
confidence: 99%
“…This ornamental plant has been known for a long time as a producer of essential oils, especially for use as a raw material for making perfume and soap. Even now, it has penetrated the air freshener and clothing fragrance industry (Agarwal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These materials were reported to have the ability to calm the central nervous system, thereby aiding in the treatment of insomnia caused by stress, anxiety, tension, and depression (Dewi et al, 2021; Setyoadi & Kushariyadi, 2011). A recent study showed that after the administration of essential oil aromatherapy intervention, the respondents experienced a significant improvement in sensations of comfort and relaxation ( Agarwal et al, 2022 ). Peppermint and citrus had been shown to have the ability to stimulate sensors and receptors, affect other organs, produce a strong emotional response, and provide a synergistic boost in energy and focus ( Sowndhararajan & Kim, 2016 ; Kennedy et al, 2018 ; Koyama & Heinbockel, 2020 ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Essential oils extracted from citrus peels have been found to have a variety of beneficial effects. [20] The antimicrobial properties of citrus essential oils are widely reported against the growth of harmful bacteria and fungi. [21,22] Anti-inflammatory effects are also attributed to the essential oils and compounds including limonene and linalool.…”
Section: Introductionmentioning
confidence: 99%
“…The essential oils derived from the Citrus peels are the prime source for the Limonene. Essential oils extracted from citrus peels have been found to have a variety of beneficial effects [20] . The antimicrobial properties of citrus essential oils are widely reported against the growth of harmful bacteria and fungi [21,22] .…”
Section: Introductionmentioning
confidence: 99%